2013
DOI: 10.31403/rpgo.v59i4
|View full text |Cite
|
Sign up to set email alerts
|

Incidencia de tuberculosis en gestantes en el Hospital Nacional Cayetano Heredia 2001-2009

Abstract: Objetivos: Determinar las complicaciones perinatales que presentan las mujeres que cursan con tuberculosis (TBC) durante la gestación y la incidencia de tuberculosis congénita en nuestro hospital durante los años 2001 a 2009. Diseño: Estudio descriptivo observacional transversal de tipo retrospectivo. Institución: Hospital Nacional Cayetano Heredia. Participantes: Gestantes con diagnóstico de tuberculosis. Intervenciones: Ingresaron al estudio todas aquellas gestantes con diagnóstico de tuberculosis que cumplí… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…In this study, we observed that 19.6% of newborns with SGA were born from mothers with pulmonary TB. These figures contrast with the 10.21% reported in the Miranda-Flores study at the INMP, Peru [11] ; 30.4% in the Montalvo study at the Cayetano Heredia National Hospital, Peru [17] ; and 19.71% in the Lin study in Taiwan, another country with a high TB rate [16] .…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…In this study, we observed that 19.6% of newborns with SGA were born from mothers with pulmonary TB. These figures contrast with the 10.21% reported in the Miranda-Flores study at the INMP, Peru [11] ; 30.4% in the Montalvo study at the Cayetano Heredia National Hospital, Peru [17] ; and 19.71% in the Lin study in Taiwan, another country with a high TB rate [16] .…”
Section: Discussionmentioning
confidence: 71%
“…Lower figures have been reported in other studies, such as those of Lin (8.0%) [16] and El-Messidi (8.4%) [10] . Montalvo, found an incidence of 17.4% of preterm infants [17] , while Miranda reported 18.4% [11] , with both studies conducted in Peru.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation